ВЛИЯНИЕ ФТОРА НА ОБРАЗОВАНИЕ УПОРЯДОЧЕННЫХ И РАЗУПОРЯДОЧЕННОЙ МОДИФИКАЦИЙ ВЕЗУВИАНА: ИССЛЕДОВАНИЕ МЕТОДОМ ИК-СПЕКТРОСКОПИИ - Боровикова Е.Ю.; Куражковская В.С. (My University, 2006)
IR spectroscopy method was used to investigate within Si-О and OH regions the so-called uncommon vesuvianites: low symmetrical ones (space group PAIn) from skarns and the high symmetrical vesuvianites (P4/nnc) but with partly ordered structure. The study has shown decisive role of fluorine in formation of these minerals. The presence of disordered domains in structures of the low symmetrical specimens from skarns indicates their high temperature origin and the ordering under slow cooling down from those high temperatures without or with poor content of fluorine (0.4-0.5 a. p. f. u.). With the middle contents of fluorine (1.0-1.6 a. p. f. u.) the high symmetrical skarn vesuvianites contain ordered domains in their structure, including domains ordered according to the acentric low. The presence of boron in composition of vesuvianite leads to strong disordering of its structure.